14-Helical folding in a cyclobutane-containing β-tetrapeptide - Izquierdo, Sandra (2004)
The efficient synthesis of tetrapeptide 5 containing, in alternation, cyclobutane and β-alanine residues is described. NMR experiments both at low temperature in CDCl3 and at 298 K in DMSO-d6 solutions show the contribution of a strong hydrogen bond in the folded major conformation of 5. Temperature coefficients and diffusion times point out a hydrogen bond involving the NH proton from the cyclobutane residue 1 whereas NOEs manifest the high rigidity of the central fragment of the molecule and are compatible with a 14-membered macrocycle. Theoretical calculations predict a most stable folded conformation corresponding to a 14-helix stabilized by a hydrogen bond between NH10 in the first residue and OC25 in the third residue. This structure remains unaltered during the molecular dynamics simulation at 298 K in chloroform. All these results provide evidence for a 14-helical folding and reveal the ability of cis-2-aminocyclobutane carboxylic acid residues to promote folded conformations when incorporated into β-peptides.